2020
DOI: 10.1096/fj.202001355rr
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for distinct quality control mechanisms of GABA B receptor during evolution

Abstract: Cell surface trafficking of many G protein-coupled receptors is tightly regulated. Among them, the mandatory heterodimer GABA B receptor for the main inhibitory neurotransmitter, γ-aminobutyric acid (GABA), is a model. In mammals, its cell surface trafficking is highly controlled by an endoplasmic reticulum retention signal in the C-terminal intracellular region of the GB1 subunit that is masked through a coiled-coil interaction with the GB2 subunit. Here, we investigate the molecular basis for the export of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…Both dGB1 and dGB2 are homologous to mammalian GABA B receptors and the conserved nature of their intracellular trafficking has very recently been investigated. 28 dGB3 is ~47% amino acid sequence similar to human GABBR2 22 and is expressed in a similar, albeit slightly different, spatiotemporal pattern to Rdl. 29 Like mammals, the fly GABA B receptors play a role in behavioral response to alcohol.…”
Section: Gamma Aminobutyric Acid (Gaba) Receptorsmentioning
confidence: 97%
“…Both dGB1 and dGB2 are homologous to mammalian GABA B receptors and the conserved nature of their intracellular trafficking has very recently been investigated. 28 dGB3 is ~47% amino acid sequence similar to human GABBR2 22 and is expressed in a similar, albeit slightly different, spatiotemporal pattern to Rdl. 29 Like mammals, the fly GABA B receptors play a role in behavioral response to alcohol.…”
Section: Gamma Aminobutyric Acid (Gaba) Receptorsmentioning
confidence: 97%
“…Despite some evidence suggesting the possible roles for COPII vesicles in the ER export of some GPCRs, 16 , 47 , 48 , 49 , 50 there remains no direct evidence indicating that nascent GPCRs are actively recruited to and concentrated in COPII vesicles. Although several motifs or sequences have been shown to be important for GPCR export from the ER, 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 none of them have been proven to directly act on receptor recruitment to COPII vesicles. Here, we have demonstrated that angiotensin II (Ang II) receptors and the chemokine receptor CXCR4 are concentrated at the ERES and COPII vesicles through distinct motifs and this concentrative process affects receptor anterograde transport from the ER through the Golgi to the PM.…”
Section: Introductionmentioning
confidence: 99%
“…Agonists (GABA and baclofen) and antagonists (CGP54626) bind to the extracellular domain of GB1 to control G protein activation by the seven-transmembrane (7TM) domain of GB2 ( 22 ). The GB2 subunit is also important for exporting GB1 to the plasma membrane ( 23 ). Some positive allosteric modulators (PAMs), such as CGP7930, display agonist activity that leads to G i/o protein–dependent signal activation ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%